2018
DOI: 10.3390/su10061957
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Oasis Expansion and Its Impact on Oasis Landscape Patterns in the Southern Margin of Tarim Basin, Northwest China

Abstract: Oasis landscape change and its pattern dynamics are considered one of the vital research areas on global land use and landscape change in arid regions. An agricultural oasis is the main site of food security and ecosystem services in arid areas. Recently, the dramatic exploitation of agricultural oases has affected oasis stability, inducing some ecological and environmental issues such as water shortage and land degradation. In this study, the Qira oasis on the southern margin of Tarim Basin, Northwest China, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…It is usually calculated through topographic maps or represented by the distance from land to road or market [46,47], and the impact of accessibility on land use is expressed by road accessibility and the impact degree of centre town. Human activities shape the natural landscape into a regular rectangular with distinct edges and corners, especially the agricultural land, and different sizes of plots form a checkerboard shape [27,48,49], a large number of studies have shown that agricultural land regulation can help improve land use efficiency [50][51][52].…”
Section: Construction Of Cultivated Land Evaluation Systemmentioning
confidence: 99%
“…It is usually calculated through topographic maps or represented by the distance from land to road or market [46,47], and the impact of accessibility on land use is expressed by road accessibility and the impact degree of centre town. Human activities shape the natural landscape into a regular rectangular with distinct edges and corners, especially the agricultural land, and different sizes of plots form a checkerboard shape [27,48,49], a large number of studies have shown that agricultural land regulation can help improve land use efficiency [50][51][52].…”
Section: Construction Of Cultivated Land Evaluation Systemmentioning
confidence: 99%
“…Governing hydrologic processes in the mountains and desert can be described as precipitation-runoff and runoff-evaporation, respectively (Han et al 2009). For the majority of the years from 1960 to 2010 in the Cele Oasis, the annual precipitation is < 50 mm (Cheng 1997;Li et al 2011;Liu et al 2018;Zhou et al 2018) and pan evaporation is in the range of 2100-3400 mm (Fig. 2).…”
Section: Surface Watermentioning
confidence: 99%
“…Water is essential to the formation and sustainment of oases in arid environments . Oases, naturally thriving yet fragile systems, have increasingly become locations of human habitation and modification (Ling et al 2013;Liu et al 2018). With essentially no other obtainable natural resources besides semi-fertile soil and water, agriculture is the predominant transformation to many oases (Song and Zhang 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cele Oasis is a hyper-arid zone in northwest China that receives very little rainfall. As the cropland expands rapidly in oasis in China [27], it is interesting to explore the best groundwater management practices in Cele Oasis. This, in result, may also inspire better water management in similar regions.…”
Section: Introductionmentioning
confidence: 99%